SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI DI SMK WALISONGO SEMARANG DENGAN METODE PROMETHEE BERBASIS WEB - Septiana, Aditia Wahyu; Nugroho, Atmoko (Universitas Semarang, 2022)
Currently, the determination of achievement students by SMK Walisongo Semarang is still manual. This takes a long time and a low level of accuracy because it is possible to miss observations of the criteria of prospective students. A decision support system for selecting achievement students is needed that can produce an accurate ranking of an assessment using the Promethee algorithm. The preference Ranking Organization Method For Enrichment Evaluation, commonly abbreviated as Promethee, determines the order in a multicriteria analysis. With this application, it is expected to assist the school in making decisions about choosing outstanding students with predetermined points and value limits.